KAJIAN DESAIN VISUAL PADA MASKOT ITEBA - Citra Mareta Rahmasari; Muhammad Adi Sukma Nalendra (JURNAL RUPA MATRA, 2022)
Mascot is a visual element that can symbolize the image and identity of the company. With a mascot, companies can communicate brand values ​​and talk to clients on behalf of the brand. Batam Institute of Technology (ITEBA) has been established for 3 years and continues to develop their visual elements, including the mascot. By reviewing the visual design of the ITEBA mascot, it is hoped that it can be used as a reference for designing new mascots. The research method chosen was questionnaire, interview and observation. With this report, it is hoped that it can be used as a reference for designers of ITEBA mascot character designs that represent agencies and are applied in ITEBA branding. Key words: Mascot, Character Design, Branding, ITEBA